Students’ Perception of Gamified Online Quizzes and Its Impacts on Their Classroom Engagement - Zahro Zainiah; Nanin Verina Widya Putri (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
Gamification has been very popular in educational field. As a consequence, there were many researchers interested to conduct a study on it. In order to give contribution for enriching the resources for such study, this research investigated students’ view toward the use of gamified online quizzes given by the teacher outside the classroom, as well as to examine the impact on students’ engagement in the classroom. The method used was qualitative, with questionnaires and interview as the instruments. The participants were 69 twelfth graders students of three classes who filled the questionnaires, as 9 students among them were interviewed as the representatives. Results showed that students perceived experience in using gamified online quizzes was positive. They recognized such quizzes as interactive and useful for their learning. Moreover, they were found to be engaged in using the gamified online quizzes. They showed their engagement in behavior, emotion, cognitive, and agentic Gamifikasi sudah menjadi hal yang sangat popular dalam bidang Pendidikan. Sebagai konsekuensinya, banyak peneliti yang tertarik mengadakan kajian tentang hal tersebut. Untuk berkontribusi dalam memperkaya sumber data untuk kajian serupa, penelitian ini ditujukan untuk menyelidiki pandangan siswa dalam penggunaan kuis online berbentuk permainan yang diberikan oleh guru di luar kelas, sekaligus meneliti dampaknya pada keterikatan siswa di dalam kelas. Metode yang digunakan adalah kualitatif, dengan kuisioner and wawancara sebagai alat penelitian. Peserta penelitian terdiri dari 69 siswa kelas 12 sebanyak 3 kelas yang mengisi kuisioner, dengan 9 siswa yang diwawancarai sebagai perwakilan. Hasil menunjukkan bahwa siswa merasakan pengalaman yang positif saat menggunakan kuis online berbentuk permainan. Mereka menganggap kuis tersebut menarik dan berguna untuk kelangsungan proses belajar mereka. Selain itu, siswa juga terikat penuh dalam menggunakan kuis tersebut. Mereka menunjukkan keterikatan secara perilaku, emosional, kognitif, dan agentik